Analisis Kualitas Air Sungai dan Air Limbah (Outlet) Perusahaan dengan Metode Indeks Pencemaran dan Pengaruhnya terhadap Populasi dan Jenis Ikan - Puspa Ayu Pitayati; M. Hatta Dahlan (Jurnal Penelitian Sains, 2017)
This study was aimed to examine the water quality of Gasing River and company’s wastewater (out-let) in physically and chemicallyat the boundary of Gasing Industrial Estate and comparing with the existing quality standard,to analyze the condition of waters quality of Gasing River using pollution index method, and to analyze influence of water quality towards the population and species of fish around it. The research was conducted in March - April 2017 at Gasing River, Gasing Industrial Estate of Talang Kelapa Subdistrict, Banyu-asin Regency. The study included measurement of several parameters that was taken by in-situ, water sam-pling, sampling of fish, analysis of laboratory water samples at Laboratory Technical Implementation Unit in Environmental Agency Banyuasin Regency, analyze laboratory test data of water samples, and did question-naire in research location. Site determination was done by using purposive sampling method. Result of re-search which have been done to river water parameter measurement in upstream, middle and downstream there are some parameter which do not fulfill standard quality of Governor Regulation of South Sumatera Number 16 Year 2005 such as pH, BOD and COD, while result of company's waste water (outlet) there is one parameter of water quality which do not fulfill standard of Governor Regulation Number 8 Year 2012 that is pH. Regarding the result of calculation of water quality status at research station by using pollution index (IP) method, it is found that station 1 to station 4 is in light contaminated category, while station 5 still meet the standard of quality. The results of catches at three stations in upstream, middle and downstream of Gasing Riv-er were obtained by catching fish of the same type that is seluang fish (Rasbora sp). It is in line with the sam-pling and questionnaire in research location, community in Gasing Village is very difficult to get fish in the catchment area at the boundary of Gasing Industrial Estate with the catch about 4-5 kg / month. For the growth pattern of the fish species in upstream, downstream and middle stations are allometrically negative with the value of b <3 that means, the weight growth of the seluang fish tends to be slower compared to length growth where the value of b can be influenced by environmental conditions. The result of t test on the value of b rela-tion of length of fish in upstream, middle and downstream of Gasing River showed significant influence be-tween weight and length. The determinant value (R²) of the length and the weight relationship of the fish that caught in upstream, middle and downstream of Gasing River is relatively moderate, the magnitude is in the range 0.50 - 0.70, indicated that diversity can be affected by other variables and the relationship between total length and weight of the fish are not so close